Insecticide Potential of Botanic Extracts Obtained from the Flora of the Brazilian North East Region - Soares, Thayanne Nicolly de Araújo; Oliveira, Vitor Leony Ferreira de; Dias, Geovani Gonçalves; Lima, Meridiana Araújo Gonçalves; Santos, Carlos Alberto Batista (European Scientific Journal, ESJ, 2018)
This article provides a literature review pointing out the relevance of plant extracts as an economically possible and ecologically sustainable alternative to the use of chemical compounds in the management and control of the insects in agriculture. The methodology was constituted in a literature review, through researches in Scielo and Lilacs, from 1990 to 2018. Organic farming is gaining importance in the Brazilian economy. The consumers are more and more conscious and demanding, choosing healthy foods, free from chemical residuals, deemed as harmful to the health. Botanic extracts can control insects and pathogens, providing no contamination for the soil, for the drinkable water sources, and leaving no toxic residuals in the environment. Studies focused on production and testing of these natural products deserve to be highlighted in the scientific literature. Only through the spreading of these studies, small producers and family farmers will access these informations.